Metaphors in Education-Themed Songs and its Implication in Learning - Astri Parawansa, Wanda; Nova Ali Vardani, Eka; Dzarna (Program Studi Pendidikan Bahasa dan Sastra Indonesia, 2023)
Educational-themed songs contain metaphorical language styles. Metaphor is a style used to equate something else called figuratively. The purpose of the research is to describe the types of metaphors in education-themed songs and implications in learning. Qualitative with descriptive method with data source 20 education-themed songs. Data collection techniques in the form of data reduction techniques. Data collection instruments use tools in the form of data collection tables. The data validity test technique uses the technique of increasing persistence. The results of the research found anthropomorphic metaphors 6 data, animal metaphors 6 data, metaphors from concrete to abstract 11 data, and synesthesic metaphors 6 data. In this study, metaphors from concrete to abstract were found the most. This research is implicated in Indonesian language learning at the junior high school (KD. 3.7 dana KD. 4.7) and high school (KD. 3.17 dana 4.17) levels. The implication of educational-themed songs with physical elements of poetry, namely language styles, especially metaphors. The lyrics of educational-themed songs can be implied in learning poetry. Educators can utilize it to be used as poetry learning. Based on these results, it is concluded that the song created by the author includes poetry literary works, poetry is inseparable from language style. One of the language styles found in songs is metaphor, educational themed songs can be used as learning materials at the junior and senior high school levels. Educators choose the material to be used in learning to increase students' interest which is implied in learning poetry in songs.